SIMULATION OF OPD WASTE DUMP SLOPE USING THE MORGENSTERN-PRICE METHOD IN WORK AREA OF PT. XYZ TBK. PASER DISTRICT, EAST KALIMANTAN PROVINCE - Audrey, Lizzy Evsa; Sophian, Raden Irvan; Hadian, Sapari Dwi (Faculty of Geological Engineering, Universitas Padjadjaran, 2023)
The research was conducted at a company working in the coal mining contract sector, namely PT. XYZ Tbk. OPD is located in Paser Regency, East Kalimantan. The research aims to create a slope simulation for analysis. This analysis is used to determine the safety value factor with the influence of the parameters used, with reference to the safety value factor based on safe slope criteria according to KEPMEN ESDM Number 1827 K /30/MEM/2018. Parameters in the simulation are material properties in the form of unit weight, cohesion and internal friction angle. The material used is bedrock material in the form of sandstone, and overburden material in the form of a mixture of sandstone and claystone. Engineering is carried out by considering the condition of the groundwater table, namely full saturation and the earthquake vibration coefficient, to be analyzed using the Morgenstern-Price method. The safety factor value that has been obtained in the slope simulation is 1,216, the safety factor value includes unsafe slopes which are affected by groundwater conditions and earthquake vibrations.